Physical and chemical properties of the rice straw activated carbon produced from carbonization and KOH activation processes - Mohamad Jani Saad,; Chia, Chin Hua; Sarani Zakaria,; Mohd Shaiful Sajab,; Sufian Misran,; Mohammad Hariz Abdul Rahman,; Chin, Siew Xian (Penerbit Universiti Kebangsaan Malaysia, 2019)
In this study, highly porous activated carbon was produced from rice straw by carbonization and followed by activation using potassium hydroxide (KOH). Activated carbon samples were prepared under different activation temperatures, i.e., 650, 750 and 850°C, and their physical and chemical properties were characterized accordingly. The BET surface area of the activated carbon samples was increased from 520 to 1048 m2/g with the increase of activation temperature from 650 to 850°C. These values were much higher than the non-activated rice straw carbon i.e., 1.16 m2/g. The pore sizes of the rice straw activated carbon were found to be mainly in mesopore size range of 2-50 nm. Total carbon content of the AC sample was increased from 8.35% to 31.73% with the increase of activation temperature from 650 to 850°C. XRD and Raman spectroscopy confirmed the graphite properties of the activated carbons produced. SEM images proved high porosity of the AC after KOH activation.